CHOICE-OF-COURT AGREEMENTS, THE ITALIAN TORPEDO, AND THE RECAST OF THE BRUSSELS I REGULATION. Issue 1 (29th January 2015) - Unknown
Abstract: The Recast of the Brussels I Regulation (1215/2012/EC) reforms EU law on jurisdiction in civil and commercial matters and includes long-awaited changes designed to prevent the use of the abusive tactic known as the Italian Torpedo to frustrate choice-of-court agreements. The new rules give priority in determining jurisdiction to a court designated by a prima facie valid agreement, even if litigation underway elsewhere was first in time. While this development has been broadly welcomed, it is unclear if the Recast's solution applies to related actions underway in other states as well as identical actions. Using a recent case from the Irish Supreme Court, in this article, we highlight that this possible omission could create significant problems, and calls into question the comprehensiveness of the Recast's solution to the problem of the Italian Torpedo.